1995
DOI: 10.1111/j.1467-1770.1995.tb00963.x
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Accent, Comprehensibility, and Intelligibility in the Speech of Second Language Learners

Abstract: This study examines the interrelationships among accentedness, perceived comprehensibility, and intelligi bility in the speech of L2 learners. Eighteen native speak ers (NSs) of English listened to excerpts of extemporaneous English speech produced by 10 Mandarin NSs and two English NSs. We asked the listeners to transcribe the utterances in standard orthography and to rate them for degree of foreign‐accentedness and comprehensibility on 9‐ point scales. We assigned the transcriptions intelligibility scores on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
426
7
20

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 923 publications
(510 citation statements)
references
References 25 publications
24
426
7
20
Order By: Relevance
“…This is problematic because pronunciation is considered to be an important area of L2 learning (Celce-Murcia, et al, 2010) with intelligibility being regarded as the instructional target instead of native-like pronunciation (Derwing & Munro, 2005;Munro & Derwing, 2015). In fact, pronunciation research has shown that having an accent does not impede intelligibility (Munro & Derwing, 1995), and therefore mutual understanding through intelligible speech should be the aspirational model in the L2 classroom (Couper, 2006). In order to achieve L2 learner intelligibility, experts advocate a balanced approach to pronunciation instruction that includes the teaching of individual sounds (vowels and consonants) and prosodic elements such as stress, rhythm and intonation (Grant, 2014).…”
Section: Second Language Teacher Education and Pronunciation Pedagogymentioning
confidence: 99%
“…This is problematic because pronunciation is considered to be an important area of L2 learning (Celce-Murcia, et al, 2010) with intelligibility being regarded as the instructional target instead of native-like pronunciation (Derwing & Munro, 2005;Munro & Derwing, 2015). In fact, pronunciation research has shown that having an accent does not impede intelligibility (Munro & Derwing, 1995), and therefore mutual understanding through intelligible speech should be the aspirational model in the L2 classroom (Couper, 2006). In order to achieve L2 learner intelligibility, experts advocate a balanced approach to pronunciation instruction that includes the teaching of individual sounds (vowels and consonants) and prosodic elements such as stress, rhythm and intonation (Grant, 2014).…”
Section: Second Language Teacher Education and Pronunciation Pedagogymentioning
confidence: 99%
“…Error coding has been utilized extensively to examine speech production errors, such as slips of the tongue in normal, unimpaired speakers (e.g., Boomer and Laver, 1973;Tweney et al, 1975), as well as for analyzing production errors of individuals with neurological injury (e.g., aphasia; Dell et al, 1997) and for speakers of a second language (e.g., Munro and Derwing, 1995;Izumi et al, 2004). Errors are often characterized based on how close the production is to the target, and whether they are considered an error of the phonological or lexical level of word production.…”
Section: Introductionmentioning
confidence: 99%
“…Intelligibility means whether an utterance is understood by an interlocutor or not. It is often measured by having listeners transcribe utterances (Munro & Derwing, 1995).…”
Section: Intelligibility Vs Nativenessmentioning
confidence: 99%
“…In recent years, investigations have been conducted to assess how various aspects of pronunciation make contributions to intelligibility. For example, prosodic features play an important role in both accent ratings and intelligibility scores (Anderson-Hsieh, Johnson, & Koehler, 1992;Munro & Derwing, 1995). More specifically, primary sentence stress (Hahn, 2004), word stress (Field, 2005;Zielinski, 2008) and speaking rate (Munro & Derwing, 2001) affect intelligibility.…”
Section: Intelligibility Vs Nativenessmentioning
confidence: 99%